THE ANALYSIS OF RHYMED TRANSLATION IN 20 POEMS TAKEN FROM "CHICKEN FOR THE TEENAGE SOUL III" - Aghitsni ArRidha, - (2009)
This paper entitled The Analysis of Rhymed Translation in 20 Poems Taken from "Chicken Soup for the Teenage Soul III" was aimed at investigating the translation strategies used by the translator in translating the poems according to Andre Lafevere's poetry translation strategies. Another purpose was to find out the translator's ways in rendering the message and form of the rhyme verses of poems. This study used qualitative method by using some techniques as follows: reading and comparing both the original and the translation poems and finding out strategies used by the translator in translating poetry, and having a deep analysis of rhymed translation of the poems to gain some findings and result. There were five poetry translation strategies used by the translator in translating the poems, namely phonemic translation (0.2%), literal translation (29.7%), rhymed translation (37.2%), blank verse translation (19.4%), and interpretation (13.6%).Rhymed translation had been found as the most frequent strategy used by the translator in translating the poems. Moreover, in doing a deep analysis of rhymed verses, the writer employed the rhymed translation data, both in Source Language (SL) and Target Language (TL). There were two kinds of changes, the change of meaning and the change of form, that were found in doing a deep analysis of rhymed translation. The first included meaning change (26.9%), omission (25.6%), and inclusion (20.2%). Meanwhile, the second included the change of word class form (9.7%), sound form (21%), and rhyme scheme form (13.4%). There were no extreme changes happened on rendering the message and form of the rhyme verses. It was because the percentages of all changes were not more than 50%. It indicated that most of all rhyme verses had been successfully transferred both in terms of meaning and form, from SL to TL without making too many changes.